INFLUENCE OF ACCOUNTING INFORMATION SYSTEMS, INTERNAL CONTROL, AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE WITH ORGANIZATIONAL CULTURE AS MODERATOR - Akbar, Devan; Kirana, Nanda Wahyu (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2026)
This research is conducted to examine the influence of Accounting Information Systems, Internal Control, and Work Motivation on Employee Performance at Chasan Rusdi Group. Furthermore, it also identifies whether Organizational Culture acts as a moderating variable. The study uses a quantitative method with purposive sampling, involving 70 respondents. Data were collected through an online questionnaire and analyzed using the PLS-SEM approach with SmartPLS 4.0. The findings showed that Accounting Information Systems, Internal Control, and Work Motivation had positive and significant effects on Employee Performance. However, Organizational Culture did not moderate the relationship between the independent variables and Employee Performance. This implies that employee performance improvement is more influenced by system effectiveness, control processes, and motivation than by organizational culture.